Analysis Of Positive Character Integration In SKI Learning In Industrial Era 4.0 - Muh. Syauqi Malik; Muqowim Muqowim (AIUA Journal of Islamic Education, 2020)
The industrial era 4.0 is marked by the rapid development of digital technology. Information and communication are very easy to get, the world is like in your hand. But behind a progress there is no doubt there are various weaknesses. Morals or positive characters are at stake, even though positive characters are the key to success. This paper aims to reveal the integration of positive characters in SKI learning in the industrial era 4.0. This research uses qualitative methods with data collection methods in the form of observation, documentation, and literature study. The research subjects were class V MI Salafiyah Tajungsari, Tlogowungu Subdistrict, Pati Regency, which amounted to 25 students. Data analysis was performed using the Microsoft Excel application and then interpreted, and then drawn conclusions. The results showed that students of class V MI Salafiyah Tajungsari had a humble character 92%, modest 92%, caring 92%, trustworthy 76%, critical thinking 84%, and fair 100%. Improvements must be made in the aspects of trustworthy and critical thinking so that the results are more than 90%, and appreciation for the fair aspect can reach 100%. Very good character needs to be appreciated, good character needs to be improved, and bad character needs to be given guidance so that all students are able to meet the demands of education in the industrial era 4.0.